2019
DOI: 10.33425/2639-9474.1095
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Assessment Situations in Clinical Studies: How do Nurse Mentors in Home-Based Health Care Services Experience Assessment Situations in Supervision of 2nd Year Bachelor Nursing Students?

Abstract: Purpose of the study: Describe nurse mentors` experiences in using the Learning Outcome Assessment Form in supervision of 2nd year nursing students` clinical study and teach learning outcomes` relation to practice, how roles and responsibilities of nurse mentors in the community home-based health care services affect assessment situations. Methodology: Explorative & descriptive qualitative method through focus group interview is applied. In autumn 2017 to spring 2018, focus group interviews done on nurse mento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…come to the fore. [42][43][44][45] The data of a study in Kenya concluded that 54% of the student nurses stated that mentor nurses had insufficient communication-interaction. 45 In a study conducted in Africa, it was reported that mentor-registered nurses spent very little time with the nursing students and could not afford enough knowledge/dedication to transform theoretical knowledge into practice.…”
Section: Discussionmentioning
confidence: 99%
“…come to the fore. [42][43][44][45] The data of a study in Kenya concluded that 54% of the student nurses stated that mentor nurses had insufficient communication-interaction. 45 In a study conducted in Africa, it was reported that mentor-registered nurses spent very little time with the nursing students and could not afford enough knowledge/dedication to transform theoretical knowledge into practice.…”
Section: Discussionmentioning
confidence: 99%